The relationship between dietary magnesium intake, stress level and headache in academic and administrative staff - Kılıç, Naciye; Erdem, Nihal Zekiye (Frontiers in Nutrition, 2026)
BackgroundMagnesium is an important mineral that plays a role in many biochemical reactions in the body. Since it plays a role in many mechanisms of the body, it is thought that it may also have effects on stress and headaches.MethodsThe study was conducted with the participation of a total of 150 volunteer academic and administrative staff aged between 19 and 65. Participants were evaluated through general information, anthropometric measurements, Headache Impact Test-6 (HIT-6) and Perceived Stress Level Scale-10 (PSS-10), 3-day food consumption record and frequency of consumption of magnesium-rich foods questionnaire.ResultsThe mean age of the participants was 31 ± 6.283 years for men and 28.55 ± 5.294 years for women. The Headache Impact Test-6 score was higher in the group with inadequate magnesium intake (p < 0.05). Although the Perceived Stress Level Scale-10 score was also higher in the group with inadequate magnesium intake, the result was not significant (p > 0.05). A negative correlation was found between dietary magnesium and HIT-6 and PSS-10 scores (r = −0.183, r = −0.197, respectively; p < 0.05). A positive correlation was also found between the scales (r = 0.456; p < 0.01).ConclusionThese findings suggest that lower dietary magnesium intake is associated with higher headache impact and perceived stress in academic and administrative staff.